Enhancing the Thermostability of Papain by Immobilizing on Deep Eutectic Solvents-Treated Chitosan With Optimal Microporous Structure and Catalytic Microenvironment - Lin, Kai-Peng; Feng, Guo-Jian; Pu, Fu-Long; Hou, Xue-Dan; Cao, Shi-Lin (Frontiers in Bioengineering and Biotechnology, 2020)
Deep eutectic solvents(DESs) have attracted anincreasing attention in the fields of biocatalysis and biopolymer processing. In this study, papain immobilized oncholine chloride- lactic acid (ChCl-Lac) DES-treated chitosan exhibited excellent thermostability as compared to the free enzyme. The properties of native or DES-treated chitosan and immobilized enzyme were characterized by FT-IR, SEM, surface area and pore property analysis. Like the common enzyme immobilization, papain immobilized on DES-treated chitosan resulted in a lower catalytic efficiency and a higher thermostability than the free enzyme due to the restricted diffusion. The results also revealed that DES could control the active group content, thus achieving the appropriate microporous structure of immobilized enzyme. Meanwhile, it could also help to construct the optimal microenvironment by hydrogen-bonding interaction between enzyme,chitosan and residual DES, which are benefit for maintaining anactive conformation and subsequently a high thermostability of papain. Moreover, it was found that trace DES (10 mM) significantly promoted the activity of free papain (145%). Deactivation thermodynamics study showed that the DES could enhance the thermostability of papain especially at high temperature (half-life of 7.4 h vs. 3.5 h) because of the increased Gibbs free energy of denaturation. Secondary structure analysis by circular dichroism spectroscopy (CD) agreed well with the activity and thermostability data, further confirming the formation of rigid conformation induced by a specific amount of DES. This work provides a new way of enzymeimmobilization synergistically intensified by solvents and supporting materials to achieve better microporous structure and catalytic microenvironment.